Foreign Institutional Investors – Understanding the Indian Advent - Manjunath, Mrs Vatsala; Bankar, Dr Bipin (The journal of contemporary issues in business and government, 2021)
The paper aims to tell the story of foreign institutional investors, advent in India. The study examines the nature of the FII flows into India. The study is spread across mainly four points of investigation. It attempts to understand if there was a significant change in the flow of FII investment before and after the economic crisis of 2008.The study intends to investigate if investments made in India, by FIIs of different countries are significantly different, quantum of investment made by FIIs in different Industrial sectors significantly differ, if there is significance of difference between the FII and DII investment flows. Data form the website of NSDL and SEBI was used in the study . FII & DII fund flows, in India, of the last 27 years have been used for the study. Based on the results of the test conducted it was concluded that there is no significant statistical difference in the quantum of FII flows before and after the financial crisis of 2008.The amount invested by the FII’s in various Industrial sectors in India, was found to be significantly different. There was no significant difference in the yearly investments made by different countries investing in India. The difference between the flows of FII and DII in India was found to be insignificant and negatively correlated. The current study could be extended in the future to study the impact of FII on the Indian retail investors’ investment choices. More study on whether the retail investors follow the investment pattern of the FII and DII needs to be done. A predictive model for the investor could be devised, to make better investment choices, by following the foreign institutional investor and domestic institutional investors.